Fluorine-Doped Carbon Coated LiFePO3.938F0.062 Composites as Cathode Materials for High-Performance Lithium-Ion Batteries - Yan, Zhixiong; Huang, Dequan; Fan, Xiaoping; Zheng, Fenghua; Pan, Qichang; Ma, Zhaoling; Wang, Hongqiang; Huang, Youguo; Li, Qingyu (Frontiers in Materials, 2020)
Fluorine-doped carbon coated olivine LiFePO4-xFx composite (LFPF/CF) is synthesized by a simple solid-state reaction method, and the Tween 40 and polyvinylidene fluoride were used as carbon source and fluorine sources, respectively. Benefiting from the Tween 40 is attributed to formation a homogeneous carbon layer on the surface of LiFePO4 particles. And polyvinylidene fluoride could produces fluoride in the thermal decomposition process, which is doped into carbon and LiFePO4 to form fluoride-doped carbon layer and LiFePO4-xFx, respectively. In this constructed architecture, the F-doped carbon layer acts as conductive network for LFP, which can enhance the electronic conductivity of overall electrode. Furthermore, the crystal lattice of LFP was enlarged by the F doping, which facilitates the Li+ intercalation/deintercalation. On the other hand, a strong electronic coupling between F-doped carbon and LiFePO4-xFx can effectively suppress the shedding of carbon layer during cycling process, which keep stabilized of the reaction interface, and thus enhance the cycling stability. As a result, LFPF/CF composite shows superior rate performance (164.8, 159.2, 148.6, 135.8 and 102.3 mAh g-1 at 0.1, 0.5, 1, 2, 5 and 10 C), and excellent cycling stability (high capacity retention of 95.6% after 500 cycles at high rate of 5 C).